Literature Review : Faktor, Hambatan, Serta Aksesibilitas yang Berkaitan dengan Health Seeking Behavior Pada Pasien Penderita HIV - Sophy Wulandari; Rima Putri Ramadhani; Indah Laily Hilmi (Jurnal Sehat Mandiri, 2024)
Human immunodeficiency virus (HIV) is one of the health problems in the world that is quite a lot of sufferers in various countries. According to data from the UNAIDS Global Report in 2018, more than 37.9 million people live with HIV, and 770 thousand people have lost their lives due to HIV / AIDS. The prevalence of mortality is also influenced by the health seeking behavior of HIV sufferers. This study aims to explore the factors, barriers, and accessibility associated with health seeking behavior in HIV patients. The method used was a qualitative method, by analyzing 9 articles that met the inclusion and exclusion criteria from 182 literature studies found in PubMed and Scopus. The results of the analysis showed factors, barriers, and accessibility that influence health seeking behavior in HIV patients. These factors included economic factors, education, perceptions of HIV, medical pluralism, partner concerns, family support, community stigma, asymptomatic HIV status, travel distance, transportation costs, breach of confidentiality, mistreatment from health services, and lack of information regarding HIV health services. It is hoped that future research can continue research related to health seeking behavior factors, as well as develop strategies to overcome barriers and improve accessibility of health services for HIV patients.